Mass and energy integration study of hydrothermal carbonization with anaerobic digestion of sewage sludge. (April 2021) - Aragón-Briceño, C.I.; Ross, A.B.; Camargo-Valero, M.A.
Abstract: Anaerobic Digestion is the most common process used for energy generation from sewage sludge but only one half of the sewage sludge is susceptible to biodegradation. Hydrothermal Carbonization is considered an option for harness all the energy embedded in sewage sludge because of its high-value products (Hydrochar and Process waters). The integration AD followed by HTC is a recent approach that is still under development. The challenge is to provide evidence for coupling HTC with the existing infrastructure at wastewater treatment works. In this work, a mass and energy integration study of the potential of coupling HTC with AD for sewage sludge treatment was evaluated. Six proposed process configurations were built using primary sludge, secondary sludge and a mix, in order to evaluate net waste generation, fate of nutrients, net energy production and potential economic benefits. The proposed scenarios showed an overall total solid and COD reduction up to 68 and 66% respectively. The inclusion of hydrochar as a fuel source increased the net energy production 10 times compared when only biogas is considered as an energy source. The potential struvite production ranged from 0.02 to 0.06 kg per tonne of sludge treated. Scenarios with 250 °C thermal treatment temperature provided better economic benefits when struvite and hydrochar are considered. Graphical abstract: Image 1 Highlights: Mass and Energy balance of the HTC-AD integration are presented. Six HTC-AD scenarios with different process temperature and sewage sludge were evaluated. Scenarios assessed with 250 °C process temperature showed higher energy and economic benefits. Scenarios with MIX sludge stream showed to be the most suitable option for HTC-AD integration.